The impact of climate on life satisfaction - David Maddison; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2010)
We analyse the influence of climate on average life satisfaction in 87 countries using data from the World Values Survey. Climate is described in terms of 'degree-months' calculated using an optimally-selected base temperature of 65°F (18.3°C). Our results suggest that countries with climates characterised by a large number of degree-months enjoy significantly lower levels of life satisfaction. This finding is robust to a wide variety of model specifications. Using our results to analyse a particular climate change scenario associated with the IPCC A2 emissions scenario points to major losses for African countries, but modest gains for Northern Europe.
Keywords: D60; H41; I31; Q51; Q54; 330; climate; climate change; happiness; life satisfaction; survey data; Klima; Zufriedenheit; Klimaveränderung; Welt